Growth, Flowering Time and Quality of Twelve Apple Varieties under Urmia Climate - Reza Rezaee; Ghasem Hasani; Seyed Edris Salehi (Majallah-i ̒Ulum-i Bāghbānī, 2017)
Introduction: Apple is a major commercial fruit crop grown in Iran. The country produces approximately 1.6 - 2.7 million tonnes of apples and was one of the top 10 apple producing countries in the world during the last decade. West Azerbaijan province, with more than 50,000 hectare of apple orchards and by producing of approximately one million tonne of fresh apple, is one of the main regions of apple production in Iran. In this region, two common apple cultivars Red Delicious and Golden Delicious are dominant (>90%), which needs to be updated by new apple cultivars to satisfy different technical/management as well as worldwide marketing requirements. Apple cultivars evaluations was started in Iran since 1953 and a lot of apple collection were established, but and until new apple cultivar was not introduced to farmers, As a first step for introduction of alternative cultivars, in this study, vegetative growth, flowering time, fruit ripening time as well as fruit quality of 12 apple (Malus pumilla Mill) cultivars were evaluated under Urmia climatic conditions. Therefore, the main objective of this study was to evaluate vegetative growth, quality and compatibility of some apple cultivars to allow selection of alternative cultivars for commercial apple production in the northwest province of Iran. Materials and methods: This experiment was conducted at the Kahriz Horticultural Research Station located in Urmia-Iran (latitude 44°07' E; 37º 53' N.; altitude, 1325 m above sea level). The experimental design was randomized complete blocks, with 12 treatments (cultivars) and three replications. The apple cultivars including Golden Delicious, Red Delicious, Red Spur, Fuji, Delbar Stival, Golden Smothee, Jonagold, Gholab-Kohanz, Golab-Kermanshah, Mahali Shikhi and Shafie Abadi were grafted on MM 111 rootstock. Trees were 10-year-old with a planting distance of 3 x 4 m and were trained as modified leader system. Data collected for annual shoot growth, time of blooming as well as fruit quality traits for one growth season and all data obtained from the trial were analysed using combined ANOVA and means were compared using the Duncan's Multiple Range Test (DMRT). SPSS (version 20) was used to analyse the data. Results and Discussion: Analysis of variance showed that apple cultivars were significantly different for all traits. Based on the means comparison test, the most and least annual shoot growth was observed in Red Delicious and Red Spur with 51.80 and 26.23 cm, respectively. The studied apple cultivars were ranked in three and five groups in terms of flowering and fruit ripening time, respectively. Flowering time is important for breeding as well as pollination purposes and in this regard there were significant differences among cultivars. The highest and the lowest fruit weight 236.07 and 63.28 g was obtained from Red Delicious and Mahale Sheikhi, respectively. The highest fruit firmness was observed in Fuji (9.17), followed by Golab Kermanshah (9.13), Red Delicious (9.03) and Golden Delicious (8.76). The highest (18.6%) TSS was observed in Fuji cultivar followed by Red Delicious (17.00%), and the lowest TSS was observed in all of early ripening cultivars. Titratable acidity (TA) was also significantly different among cultivars with Fuji showing the highest (1.32) and Golab Kermanshah, Golab Kohanz and Golshahi were the lowest (0.31-0.44) values. Compared to the other cultivars, Red Spur and Jonagold with a more L/D ratio (0.91) showed an elongated fruit form. Fruit shape especially the ratio of L/D has an important role in marketing. In addition, due to low growth and dense canopy as well as good fruit quality, the two recent cultivars are recommended for high density planting. Conclusion: Final ranking of cultivars based on cumulative ranks from different traits showed that the higher ranks for Fuji, Red Spur and Goden Smothee, indicating their higher potential as an alternative to the Red and Golden delicious. Among the evaluated cultivars, three cultivars including Jonagold, Golshahi and Delbar Stivel were the best option to fulfill market demands for fresh fruit during mid-summer trough early autumn. It should be emphasized that these cultivars may be suitable for similar climates, but because of the effects of growing conditions (i.e. soil type, climate, cultural practices etc.) on the results of cultivar evaluation projects, complementary trials should be done in other regions before commercial planting commences. Continuous evaluation of new apple cultivars is an important prerequisite for sustainable apple industry.